A study of methods to improve the performance of drag bits used to cut hard rock - Hood, Michael (My University, 2015)
No abstract
A Thesis Submitted to the Faculty of Engineering University of Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy. Johannesburg 1977
Keywords: Drag bits (Drilling and boring)